STUDENT’S PERCEPTION TOWARD CAPTIONED MOVIE AS LEARNING STRATEGY IN ENGLISH PRONUNCIATION CLASS (RETAIN, 2023)
Pronunciation is one of the crucial elements in the language framework that supports proper interaction. However, several researchers have discussed the challenges of teaching and learning pronunciation, especially for ESL learners. Teachers must provide effective learning strategies for students to follow the latest English standards. The goal of this achievement is that students can overcome communication barriers in using the English language. This study aims to determine students' perceptions of a specific strategy that involves audio-visual media to enhance students' achievement in pronunciation class. The audio-visual media used in this research is an original English movie with an English caption provided. The subject of this study involved 30 students from grade 9 in a particular junior high school. The research data was taken using a Likert scale questionnaire. The data show positive results on students' perception of using audio-visual media called